Discrete Modes of Life Cycle in Velarifictorus micado Species Complex (Orthoptera: Gryllidae). (18th December 2013) - He, Zhuqing; Takeda, Makio
Abstract : Different modes of climatic adaptation often lead to a split in reproductive cohesion and stimulate speciation between populations with different patterns of life cycle. We here examined egg development and photoperiodic adaptations in the nymphal development of Velarifictorus micado . We defined fast hatching populations as nymphal diapause and slow hatching populations as egg diapause. The nymphs were reared under two photoperiods, LD 16 : 8 and LD 12 : 12 at 27.5°C, and the mean days of nymphal development were compared. The results indicate that the nymphal diapause populations showed slower nymphal development under LD 12 : 12 than under LD 16 : 8, and this retardation increased with the increase of original latitude. The egg diapause populations showed slower nymphal development under LD 16 : 8 than under LD 12 : 12. These features help synchronizing their overwintering stages. Gene flow from the opposite forms may disturb this synchronization mechanism, and therefore natural selection should favor displacement of the two forms. This could be an incipient climatic isolation mechanism of reproductive stage.